Distinctive Patterns of Flavonoid Biosynthesis in Roots and Nodules of Datisca glomerata and Medicago spp. Revealed by Metabolomic and Gene Expression Profiles - Gifford, Isaac; Battenberg, Kai; Vaniya, Arpana; Wilson, Alex; Tian, Li; Fiehn, Oliver; Berry, Alison M. (Frontiers in Plant Science, 2018)
Plants within the Nitrogen-fixing Clade of Angiosperms form root nodule symbioses with nitrogen-fixing bacteria. Actinorhizal plants (in Cucurbitales, Fagales, Rosales) form symbioses with the actinobacteria Frankia while legumes (Fabales) form symbioses with proteobacterial rhizobia. Flavonoids, secondary metabolites of the phenylpropanoid pathway, have been shown to play major roles in legume root nodule symbioses: as signal molecules that in turn trigger rhizobial nodulation initiation signals and acting as polar auxin transport inhibitors, enabling a key step in nodule organogenesis. To explore a potentially broader role for flavonoids in root nodule symbioses across the Nitrogen-fixing Clade, we combined metabolomic and transcriptomic analyses of roots and nodules of the actinorhizal host Datisca glomerata and legumes of the genus Medicago. Patterns of biosynthetic pathways were inferred from flavonoid metabolite profiles and phenylpropanoid gene expression patterns in the two hosts to identify similarities and differences. Similar classes of flavonoids were represented in both hosts, and an increase in flavonoids generally in the nodules was observed, with differences in flavonoids prominent in each host. While both hosts produced derivatives of naringenin, the metabolite profile in D. glomerata indicated an emphasis on the pinocembrin biosynthetic pathway, and an abundance of flavonols with potential roles in symbiosis. Additionally, the gene expression profile indicated a decrease in expression in the lignin/monolignol pathway. In Medicago sativa, by contrast, isoflavonoids were highly abundant featuring more diverse and derived isoflavonoids than D. glomerata. Gene expression patterns supported these differences in metabolic pathways, especially evident in a difference in expression of cinnamic acid 4-hydroxylase (C4H), which was expressed at substantially lower levels in D. glomerata than in a Medicago truncatula transcriptome where it was highly expressed. C4H is a major rate-limiting step in phenylpropanoid biosynthesis that separates the pinocembrin pathway from the lignin/monolignol and naringenin-based flavonoid branches. Shikimate O-hydroxycinnamoyltransferase, the link between flavonoid biosynthesis and the lignin/monolignol pathway, was also expressed at much lower levels in D. glomerata than in Medicago truncatula. Our results indicate a) a likely major role for flavonoids in actinorhizal nodules, and b) differences in metabolic flux in flavonoid and phenylpropanoid biosynthesis between the different hosts in symbiosis.